The use of social media among Indonesia’s Migrant Workers (IMWs) - Citra Hennida; Kandi Aryani; Sri Endah Kinasih (Masyarakat, Kebudayaan dan Politik, 2021)
Netizens often use social media as a medium for activism, including Indonesia’s Migrant Workers (IMWs). Social media with networked characteristics has succeeded in lifting narratives in particular groups that have not been heard a lot and have escaped mainstream media scrutiny. Starting from the development of communication between IMWs, we raise the extent to which IMWs use social media as a medium for social activism, especially for IMWs protection issues and social media’s main content uploaded IMWs. This study aims to analyze to what extent social media is used by IMWs for social activism related to issues concerning the protection of migrant workers and what influences their behavior when using social media. We use a social media activism framework within the social media platform. Researchers collected data from March-October 2019 through participant observation, in-depth interviews, and focused discussions that presented 15 representatives from assistants, NGOs, and academics in Malang. There were also 25 IMWs representatives with placement experience in Hong Kong, Taiwan, Malaysia, and Saudi Arabia. We found that the majority of IMWs use social media as a means of communicating between themselves and their families in the country; however, social media content for social activism is low, especially for the issue of IMWs protection. The culture and legal system in the countries of origin and destination countries influence the low level of participation in the content they create. IMWs is placed in a country with a more open culture, where local laws are more apparent in the protection of IMWs, so IMW’s social media content is more open and willing to provide testimony on the problems that exist around them and vice versa. Therefore, although social media is massive among IMWs, it is not linear with content production that leads to protection.